Implementation of Teamwork in Students Using the Improvement Model Cycle at the Ibnu Sina Nursing Academy, Sabang City - Gressia, Rosa Galica Gita; Khairunisa, Aida; Aldani, Noor Asnidar; Al Kautsarina, Vara; Herdianto, Pulung (Mata Pena Madani, 2025)
Nurses experience unexpected events due to a lack of non-technical skills, such as teamwork, which plays a crucial role in improving patient safety. This study aims to enhance the skills of nursing students in Sabang City in implementing teamwork through simulation methods. A quasi-experimental method with a pretest-posttest design without a control group was used to evaluate the effectiveness of teamwork implementation among 20 nursing students through the